Investigating Barriers to Promoting Oral Health in Students with hearing impairment from Mothers' Perspective: A Qualitative Content Analysis - Bahadorimonfared, Zahra; Ghorbani, Zahra; Rojhanian, Tayebe; Pakkhesal, Mina; Shafiei, Sediqe (Journal of Dental School, 2023)
Objectives Studies have shown the high prevalence of dental caries, negligence of oral health, and unmet dental care needs among children with hearing impairment compared to their healthy peers. This study was conducted to determine the barriers to oral health of children with hearing impairment from the perspective of their mothers. Methods In this qualitative study, semi-structured interviews were conducted with 19 mothers based on purposive sampling in order to investigate the factors affecting compliance with oral health. Interviews were recorded, handwritten, coded and classified; and for content analysis, Graneheim and Lundman's qualitative approach was used. Results As a result of the data analysis, the three main themes of “the effects of general health status, the effects of instruction and learning, and problems in receiving dental health care services” were identified as barriers to good oral health. Moreover, nine sub-themes of “inadequate education regarding oral health, parental insufficient supervision, shortages in dentistry service delivery systems, obstacles hindering mother from pursuing services, lack of guidelines for offering free periodical dental examinations for children with special needs, the impact of improper nutritional habits on oral health, children’s mental problems, unfavorable oral health conditions, and the impact of oral health on the child’s general health" were obtained. Conclusion Inadequate education in the field of oral health and difficulties in receiving dental services were identified as the most important factors affecting oral health in children with hearing impairment from their mothers' perspective. .